2017
DOI: 10.2139/ssrn.3159123
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Unicorn: Predicting Early Stage Startup Success Through a Hybrid Intelligence Method

Abstract: Artificial intelligence is an emerging topic and will soon be able to perform decisions better than humans. In more complex and creative contexts such as innovation, however, the question remains whether machines are superior to humans. Machines fail in two kinds of situations: processing and interpreting "soft" information (information that cannot be quantified) and making predictions in "unknowable risk" situations of extreme uncertainty. In such situations, the machine does not have representative informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 71 publications
0
28
0
1
Order By: Relevance
“…At the same time, taking 35 cities in China as research samples, through principal component analysis and cluster analysis, she found the important role of human resources in the cultivation of Unicorns [23]. Delermann developed a hybrid intelligence method based on the concept of human-computer complementarity to identify whether a start-up has grown into a Unicorn and pointed out that talent and policy resources are the most important input elements [24]. Stemler took the Unicorn Airbnb as a case study and then found that cumbersome enterprise regulatory rules hindered its rapid growth.…”
Section: Research Review and Analysis Frameworkmentioning
confidence: 99%
“…At the same time, taking 35 cities in China as research samples, through principal component analysis and cluster analysis, she found the important role of human resources in the cultivation of Unicorns [23]. Delermann developed a hybrid intelligence method based on the concept of human-computer complementarity to identify whether a start-up has grown into a Unicorn and pointed out that talent and policy resources are the most important input elements [24]. Stemler took the Unicorn Airbnb as a case study and then found that cumbersome enterprise regulatory rules hindered its rapid growth.…”
Section: Research Review and Analysis Frameworkmentioning
confidence: 99%
“…On the other hand, collective human input combines the input of several individual humans by leveraging mechanisms of human computation (e.g. [68,66,67]). This approach allows to reduce errors and biases of individual humans and the aggregation of heterogeneous knowledge [45,69,65].…”
Section: Human-ai Interactionmentioning
confidence: 99%
“…Random forest achieves the higher performance compared to other method in sentiment analysis. Dellermann, et al [22] Semi-supervised method is used in this research.…”
Section: Literature Work On Startup Prediction Performancementioning
confidence: 99%